Plasmid preparations in gene therapy - Małecki, Maciej (Contemporary Oncology/Współczesna Onkologia, 2004)
Plasmid vectors are commonly used preparations in gene therapy trials. Over 20% of all clinical trials were performed with plamids (non-viral system). Gene preparations very often look like a standard drug product described in classical pharmacology. DNA, a therapeutic gene, seems to be an active substance of the drug and the vector is a carrier of the therapeutic gene. Plasmid vector allows for the efficient transfer and expression of genes. Gene therapy plasmid production is not different from the production of other vectors. Generally, the plasmid preparations are isolated from transformed Escherichia coli bacteria in the basic conditions, and the chromatography methods are very useful for further efficient purification of the plasmid vectors. The clinical product must be manufactured in compliance with GMP in facilities authorized by national regulatory agencies. The quality of the isolated plasmid must be determined in various biochemical, microbiological, toxicological and pharmacological analysis performed in vitro as well as in vivo. Clinical grade plasmid preparation can be used in the clinical conditions only. Plasmid preparations are widely used in gene therapy applications. Cancer gene therapy as well the classical gene therapy – correction of genetic defects – require plasmids. In the cancer gene therapy very often the immunostimulatory, proapoptotic and antyangiogenic genes are cloned into vectors and transfected in vivo.